3-Bromopyruvate: A New Targeted Antiglycolytic Agent and a Promise for Cancer Therapy - Ganapathy-Kanniappan, S.; Vali, M.; Kunjithapatham, R.; Buijs, M.; Syed, L.H.; Rao, P.P.; Ota, S.; Kwak, B.K.; Loffroy, R.; Geschwind, J.F. (Current Pharmaceutical Biotechnology, 2010)
The pyruvate analog, 3-bromopyruvate, is an alkylating agent and a potent inhibitor of glycolysis. This antiglycolytic property of 3-bromopyruvate has recently been exploited to target cancer cells, as most tumors depend on glycolysis for their energy requirements. The anticancer effect of 3-bromopyruvate is achieved by depleting intracellular energy (ATP) resulting in tumor cell death. In this review, we will discuss the principal mechanism of action and primary targets of 3-bromopyruvate, and report the impressive antitumor effects of 3-bromopyruvate in multiple animal tumor models. We describe that the primary mechanism of 3-bromopyruvate is via preferential alkylation of GAPDH and that 3- bromopyruvate mediated cell death is linked to generation of free radicals. Research in our laboratory also revealed that 3- bromopyruvate induces endoplasmic reticulum stress, inhibits global protein synthesis further contributing to cancer cell death. Therefore, these and other studies reveal the tremendous potential of 3-bromopyruvate as an anticancer agent.
Keywords: anti-metabolite